Enhancing cubosome functionality by coating with a single layer of poly-epsilon-lysine - Deshpande, Sonal; Venugopal, Edakkal; Ramagiri, Shobha; Bellare, Jayesh R.; Kumaraswamy, Guruswamy; Singh, Neetu (ACS Applied Materials & Interfaces, 2014)
We report the preparation and characterization of monoolein cubosomes that can be easily surface modified through adsorption of a single layer of cationic poly-epsilon-lysine. Poly-epsilon-lysine coated cubosomes show remarkable stability in serum solution, are nontoxic and, are readily internalized by HeLa cells. The poly-epsilon-lysine coating provides chemical handles for further bioconjugation of the cubosome surface. We also demonstrate that the initial release rate of a hydrophilic drug, Naproxen sodium, from the cubosomes is retarded with just a single layer of polymer. Interestingly, cubosomes loaded with Naproxen sodium, recently shown to have anticancer properties, cause more apoptosis in HeLa cells when compared to free unencapsulated drug.
Keywords: bioconjugation; cubosomes; drug delivery vehicle; dual loading; theranostics

Mitigating the cytotoxicity of graphene quantum dots and enhancing their applications in bioimaging and drug delivery - Chandra, Anil; Deshpande, Sonal; Shinde, Dhanraj B.; Pillai, Vijayamohanan K.; Singh, Neetu (ACS Macro Letters, 2014)
Despite the promising photophysical properties of fluorescent graphene quantum dots (GQDs), their cellular toxicity needs to be addressed before their full potential could be completely realized in biomedicine. A simple method for mitigating the toxicity of GQDs by embedding them in PEG matrix is reported here. The enhanced biocompatibility of polymer modified, P-GQDs, is attributed to reduced reactive oxygen species generation, as measured by an intracellular ROS assay. We also demonstrate the enhanced loading and efficient intracellular delivery of therapeutics by P-GQDs.